Pengembangan Model Project Based Learning Dalam Sistem Informasi Managemen Untuk Memperkuat Literasi Teknologi - Putu Eka Wati; I Wayan Putrawan; I Putu Bayoe Maha Putra (Universitas Pendidikan Ganesha, 2022)
Technological advances have received great attention from all sectors to improve the sustainability of life today. At this time people are forced to master technology or better known as technological literacy. Presidential Decree No. 8 of 2012 concerning KKNI, which focuses on CPL (achievement profile of graduates who will later be billed as learning outputs. The output of the management information system course is expected to be able to design and implement data-based information technology infrastructure to realize information resilience oriented to community needs and technological developments This study aims to determine the feasibility of teaching materials for management information systems based on project-based learning from the aspect of content, language, design and determine the feasibility of teaching materials in group trials. The subjects of this study were Ganesha Guru Polytechnic students who took management information systems courses, While the object under study is a management information system teaching material based on project-based learning. The research was developed using the ASSURE model, with the consideration that this development model is learning-oriented. involving language, content and media experts. Each expert is given 8 instruments and provides an assessment according to the project-based learning teaching materials that have been developed. Assessment of teaching materials that have been developed from content, design and language experts shows that teaching materials that have been packaged with an average of 4.6 are in the very good category. This shows the feasibility level of management information system teaching materials developed with a project-based learning model are suitable for use among students. Student assessments are also in line with the results of the feasibility of experts. Student assessments state that the teaching materials developed are categorized as good